The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0103-21002010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Errors in medicine administration - profile of medicines: knowing and preventing

Abstract: Objectives: To describe the pharmacological characteristics of medicines involved in administration errors and determine the frequency of errors with potentially dangerous medicines and low therapeutic index, in clinical units of five teaching hospitals, in Brazil. Methods: Multicentric study, descriptive and exploratory, using the non-participant observation technique (during the administration of 4958 doses of medicines) and the anatomical therapeutic chemical classification (ATC). Results: Of that total, 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 16 publications
0
22
0
10
Order By: Relevance
“…Literature review (14) estimated that the incidence of adverse reactions in children was 4.37% to 16.78% , similar to that found in this study (10.8%). Although national studies (15,16) claim that the wrong time is the most common medication error in health care settings, this study identified a higher frequency of wrong preparation technique. This can be justified since those studies do not seem to consider wrong preparation technique as an adverse drug event.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Literature review (14) estimated that the incidence of adverse reactions in children was 4.37% to 16.78% , similar to that found in this study (10.8%). Although national studies (15,16) claim that the wrong time is the most common medication error in health care settings, this study identified a higher frequency of wrong preparation technique. This can be justified since those studies do not seem to consider wrong preparation technique as an adverse drug event.…”
Section: Discussionmentioning
confidence: 55%
“…The knowledge of the pharmacological profile could be an important strategy to be used in the prevention of medication errors in health institutions (15,18) , and may contribute to the development of educational actions for specific types of drugs such as low therapeutic index.In this study, gentamicin and amikacin were the most involved in errors related to medication administration technique.They are two aminoglycoside antibiotics with low therapeutic index and they are also nephrotoxic and ototoxic (3) . In other countries these drugs were also associated with errors occurring in neonatal intensive care unit and pediatrics (14,19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neste contexto, estudo multicêntrico realizado em cinco hospitais brasileiro acerca dos erros de medicação identificou 1500 erros, ou seja, 30% das doses administradas continham algum erro (9) .…”
Section: Metodologiaunclassified
“…According to Mendes et al (2014), such errors cause the death of 1 (one) in 131 (one hundred and thirty-one) ambulatory patients and 1 (one) in 854 (eight hundred and fifty-four) inpatients, which consists of a rate of medication errors varying from 4.8% to 5.3%. Reis et al (2010), researchers who studied the topic in Brazilian public hospitals, identified drug administration problems in 30% of cases studied.…”
Section: Introductionmentioning
confidence: 99%